Edukasi Konsumsi Tablet Fe pada Ibu Hamil dalam Mendukung Implementasi Permenkes RI Nomor 6 Tahun 2024 tentang Standar Teknis Pemenuhan SPM Kesehatan - Retnaning Muji Lestari; Serafina Damar Sasanti; Diah Winatasari; Sofita Ayuk Epiyanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia in pregnant women remains a significant health problem affecting both mother and fetus. One preventive effort is the regular consumption of iron (Fe) tablets; however, adherence is still low due to limited knowledge. This community service activity aimed to improve pregnant women’s knowledge regarding Fe tablet consumption in supporting the implementation of the Regulation of the Minister of Health of the Republic of Indonesia Number 6 of 2024 on Minimum Service Standards in Health. The methods used included lectures, question-and-answer sessions, and discussions supported by leaflets and PowerPoint, with evaluation through pre-test and post-test. Participants consisted of 13 pregnant women. The results showed an increase in the average score from 75 (pre-test) to 95 (post-test), indicating that the education provided was effective in improving knowledge. This activity is expected to enhance adherence to Fe tablet consumption and contribute to anemia prevention as well as the achievement of minimum health service standards.